The Effects of Different Text Design and Learner Cognitive Style on Learning Effectiveness and Appeal - Degeng, Made Duananda Kartika (Journal of Ecohumanism, 2024)
Elaboration model was used as a basis to develop instructional text design in this research. The models developed were the Elaboration step by step model (SM) and the Elaboration linear model (LM). The interactive effect that may occur from the previously mentioned variables was examined with learners cognitive style as a moderator and learning appeal and effectiveness as dependent variables. The proposed hypotheses were analyzed using experimental factorial design (2X2). Two groups of students were selected through cluster sampling. It was concluded that the Elaboration model with Step-by-step configuration could be more appealing and effective in the learning process. The second hypothesis indicated that, compared to field Independence students, the group of Field Independences achieved significantly higher scores. The third hypothesis showed that there was no interaction between the two variables in terms of learning effectiveness.